Development and validation of an automatic recording microcontroller-based pendulum impact cutter - PATEL, ABHISHEK; SINGH, KRISHNA PRATAP; ROUL, AJAY KUMAR; MAHORE, AMAN; NALAWADE, ROHIT DILIP; SINGH, AVESH KUMAR (The Indian Journal of Agricultural Sciences, 2023)
Knowledge of rice straw bunch in respect of cutting energy is the important factor for optimization of cutting elements in straw chopping system. A micro controller-based pendulum impact cutter was developed during 2019–21 at the ICAR-Central Institute of Agricultural Engineering, Bhopal, Madhya Pradesh. The system was integrated with load cell, adjustable pendulum arm and adjustable shear and approach angle (0–30 degree) during the cutting experiment. In this study, straw bunch cutting energy at the lowest point of Node 3 was examined which is just above the ground surface. Three type of blades SMS serrated, cutter bar and SMS plain blade were used to determine cutting energy. In order to determine the cutting energy requirement of straw bunch, the mechanical and physical properties of straw were determined. The results represent that the cutting force was significantly affected by blade type, shear angle and approach angle. The minimum cutting energy for SMS serrated, cutter bar and SMS plain blade was registered as 120, 189 and 243 J, respectively among all combinations of shear and approach angle. Developed recording type pendulum impact cutter was compared with the traditional method at selected combination of shear and approach angle for all the three blades and the relative error was recorded between 4–6%. It was concluded that with increasing approach angle at constant shear angle the cutting force initially decreased up to 20 degree and rapid increase from 20 to 30 degree of approach angle. Consequently, the SMS serrated blade emerges as the preferred choice for the rotary impact cutter development, showcasing the potential of this research in advancing straw chopping technology.